DEVELOPMENT OF A PHYSICS LEARNING ACTIVITY FOR THE TOPIC OF BOYLE’S LAW USING THE STEM APPROACH - Muhammad Amirul Rahiman; Nurulhuda Abd Rahman (Universitas Negeri Padang, 2022)
This paper reports on the development of a Physics learning activity based on the STEM approach for the topic of Boyle’s Law and the tests conducted to determine its validity and feasibility. The population of this study was fifth-semester bachelor of education in Physics students from one of the public universities in Malaysia. Nineteen participants sampled using the simple random sampling technique. Two instruments used were self-developed questionnaire for determining the content validity of the learning activity and a feasibility questionnaire adapted from the Structured Assessment of Feasibility (SAFE) questionnaire. Most of the data on feasibility shows that the activity is feasible to be implemented in schools albeit will require extra teaching and learning time and cost compared to the usual teaching and learning time and cost allocated. The research successfully developed a tested learning activity based on the STEM approach for the topic of Boyle's Law that is quite feasible. This result implies that it can be used as a reference for teachers who are interested in conducting a STEM-based lesson with the awareness that the lesson will take more time and additional cost to implement.